Prevalence and molecular epidemiology of Clostridium difficile infection in Thailand. (January 2017) - Putsathit, P.; Maneerattanaporn, M.; Piewngam, P.; Kiratisin, P.; Riley, T.V.
Abstract: Little is known about Clostridium difficile infection (CDI) in Asia generally, and specifically in Thailand. Given the high prevalence of inappropriate antibiotic usage in this region, CDI is likely to be common. This study investigated the prevalence and molecular epidemiology of CDI in Thailand. Stool specimens collected from inpatients with diarrhoea at Siriraj hospital in Bangkok ( n = 422) were cultured on ChromID Cdiff agar and any presumptive C. difficile colonies were identified, PCR ribotyped and toxin profiled. As part of the routine C. difficile testing at Siriraj Hospital, 370 specimens also underwent testing with the BD MAX Cdiff assay to detect the presence of tcdB. With direct culture, 105 different isolates of C. difficile were recovered from 23.7% (100/422) of the stool specimens. The prevalence of toxigenic and nontoxigenic isolates was 9.2% (39/422) and 15.6% (66/422), respectively. Of the toxigenic isolates, 69.2% (27/39) and 30.8% (12/39) were tcdA and tcdB positive (A + B + ), and A − B +, respectively; none contained binary toxin genes. The five most prevalent ribotypes (RTs) were 014/020 group (17/105), 010 (12/105), 017 (12/105), 039 (9/105) and 009 (6/105). Using toxigenic culture as the reference standard, the sensitivity, specificity, positive predictive value and negative predictive value of the BD MAX Cdiff assay were 68.6, 95.1, 63.2 and 96.1%, respectively. The high proportion of A − B +, RT 017 strains emphasises the need for diagnostic tests that detect either both toxins or just tcdB. Continued surveillance that involves stool culturing will allow molecular tracking and assist in elucidating the epidemiology of CDI in Thailand.